Family Handyman guide to skills, tools & techniques - Buhrmester, Jason (A Family Handyman book, 2025)
"Created by the team known for a commitment to quality, craftsmanship and overall DIY awesomeness, this must-have book is a treasure trove of essential skills and techniques for today's homeowners. Let's face it: Home DIY comes with a learning curve. And no matter how many projects you have under your toolbelt, brushing up on the essential skills, tools and techniques that pros use every day will allow you to achieve higher-quality, longer-lasting results--and save you time, trouble and money along the way. From painting hacks to carpentry tips from a pro, this new book from Family Handyman has you covered. So, whether you're a seasoned DIYer or a newbie, Family Handyman Guide to Tools, Skills & Techniques is the trusted companion every homeowner needs! Don't miss your opportunity to fine-tune the essential skills and techniques you need to improve your living spaces. A tool guide featuring an overview of some of the most common tools in your workshop, plus how to safely use them. Expert advice from the trusted team at Family Handyman magazine for honing your woodworking, carpentry, electrical skills--and more! Helpful hints and techniques for painting, replacing floors and plumbing, to name a few. Bonus projects that help you put the skills and techniques you read about to good use."--